Short-chain fatty acid receptors inhibit invasive phenotypes in breast cancer cells - Thirunavukkarasan, M.; Wang, C.; Rao, A.; Hind, T.; Teo, Y.; Siddiquee, A.; Goghari, M.; Kumar, Alan Prem; Herr, D. (Public Library of Science, 2017)
Short chain fatty acids (2 to 6 carbons in length) are ubiquitous lipids that are present in human plasma at micromolar concentrations. In addition to serving as metabolic precursors for lipid and carbohydrate synthesis, they also act as cognate ligands for two known G protein-coupled receptors (GPCRs), FFAR2 and FFAR3. While there is evidence that these receptors may inhibit the progression of colorectal cancer, their roles in breast cancer cells are largely unknown. We evaluated the effects of enforced overexpression of these receptors in two phenotypically distinct breast cancer cell lines: MCF7 and MDA-MD-231. Our results demonstrate that both receptors inhibit cell invasiveness, but through different signaling processes. In invasive, mesenchymal-like MDA-MB-231 cells, FFAR2 inhibits the Hippo-Yap pathway and increases expression of adhesion protein E-cadherin, while FFAR3 inhibits MAPK signaling. Both receptors have the net effect of reducing actin polymerization and invasion of cells through a Matrigel matrix. These effects were absent in the less invasive, epithelial-like MCF7 cells. Correspondingly, there is reduced expression of both receptors in invasive breast carcinoma and in aggressive triple-negative breast tumors, relative to normal breast tissue. Cumulatively, our data suggest that the activation of cognate receptors by short chain fatty acids drives breast cancer cells toward a non-invasive phenotype and therefore may inhibit metastasis. © 2017 Thirunavukkarasan et al.